Ostracoda from the Turonian of South-east England. Issue 655 (22nd November 2019) - Slipper, I. J.
ABSTRACT: Ostracod assemblages from 51 samples collected through the Turonian Stage of the Late Cretaceous from three cliff sections near Dover, Kent, south-east England comprise 105 species group taxa. These are described and illustrated by stereo-pair scanning electron microscopy. Part 1 is concerned with the suborders Cladocopina, Platycopina, Sigilliocopina, Bairdiocopina and Cypridocopina. The stratigraphic occurrence has been determined by examining 7877 specimens, assigned to 31 species group taxa arranged in 10 genera. Of these, 18 are referred to previously described taxa, five species and two subspecies are here described as new, and six species are left in open nomenclature, two of which are compared to previously described taxa. A modified freeze-thaw method is detailed for processing the Turonian chalks.